FAKTOR-FAKTOR PENYEBAB TERJADINYA PATOLOGI BIROKRASI DALAM PELAYANAN PUBLIK PADA DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI SULAWESI TENGGARA - Rasmin; Sarinah; La Ode Agus Said (Journal Publicuho, 2025)
This study aims to determine and analyse the factors that cause bureaucratic pathology in public services at the Manpower and Transmigration Office of Southeast Sulawesi Province. This study uses a qualitative descriptive approach, determining informants using purposive sampling with 6 informants. Data collection in this study was conducted through interviews, observations and documentation studies. The results of this study indicate that bureaucratic pathology in public services at the Manpower and Transmigration Office of Southeast Sulawesi Province is influenced by five main factors, namely managerialism, incompetence, violations, dysfunctionality, and internalisation. Although in general there are no strong indications of abuse of authority or unlawful acts, there are still bureaucratic symptoms such as a less participatory leadership style, low competence of some employees, weak work discipline, disproportionate workload, and lack of ability in utilising technology.